Gestión de tesorería de los hoteles de cuatro estrellas en la ciudad de Guayaquil - Farías Gómez, Eduardo Augusto (2018)
The present research work is carried out in order to determine at present the existing processes of internal control, since the field of accounting is a fundamental and indispensable tool for the performance and fulfillment of the objectives that each organization proposes in a determined period, and at the same time to achieve them with greater efficiency and effectiveness, giving a vision to the administrator in which way the work is being executed and to be a tool of aid in the decision making. Specifically, the present research study will focus on the areas of collections. In hotels with four stars in the city of Guayaquil, which will promote a broader vision of how these processes are being developed, and which will allow to describe the specific way in which companies are optimizing their internal control for the good performance of the activities , for a short, medium or long term goal achievement………